The Influence of Social Awareness on Social Entrepreneurship Interest in Generation Z - Adek Apriyandi (International Journal For Advanced Research, 2026)
Social entrepreneurship has emerged as an innovative approach to addressing social and environmental challenges while simultaneously creating sustainable economic value. Among the factors influencing individuals' willingness to engage in social entrepreneurship, social awareness is considered an important psychological determinant, particularly for Generation Z, who are characterized by high digital literacy and increasing concern for social issues. This study aimed to examine the effect of social awareness on social entrepreneurial intention among Generation Z. A quantitative research approach with an explanatory design was employed. Data were collected through an online questionnaire from 80 Generation Z respondents selected using purposive sampling. The collected data were analyzed using descriptive statistics and simple linear regression analysis with IBM SPSS Statistics 26. The results revealed that social awareness has a positive and statistically significant effect on social entrepreneurial intention (β = 0.684, p < 0.001). The coefficient of determination (R² = 0.468) indicated that social awareness explained 46.8% of the variance in social entrepreneurial intention, while the remaining variance was influenced by other factors not included in the model. These findings suggest that individuals with higher levels of social awareness are more likely to develop stronger intentions to establish social enterprises that generate both economic and social value. The study contributes to the growing literature on social entrepreneurship by highlighting the importance of strengthening social awareness through entrepreneurship education, community engagement, and sustainability-oriented learning programs. The findings also provide practical implications for universities and policymakers in promoting socially responsible entrepreneurship among Generation Z.